Cracking susceptibility of concrete made with coarse recycled concrete aggregates. (15th January 2016) - Adams, Matthew P.; Fu, Tengfei; Cabrera, Adal Guerra; Morales, Monica; Ideker, Jason H.; Isgor, O. Burkan
Highlights: Mixtures are examined for their susceptibility to crack due to drying shrinkage. Mixtures with natural aggregates and 25% or 100% replacement with RCA are examined. RCA mixtures had similar strengths compared to natural aggregate systems. RCA mixtures had extended times-to-cracking compared to rounded aggregate systems. RCA mixtures had lower stress rates compared to a rounded aggregate systems. Abstract: This study tested the hypothesis that concrete produced with recycled concrete aggregate (RCA) has increased cracking resistance compared to concrete incorporating natural aggregates. Two sources of RCA were used: (1) a laboratory created RCA produced by crushing previously produced laboratory concrete; and (2) a field RCA obtained from a demolished airfield pavement. Mechanical properties, and shrinkage and cracking due to drying of concrete produced with RCA replacement were studied. Adequate compressive strength (39.3–43.4 MPa), splitting tensile strength (3.7–4.4 MPa), and modulus of elasticity (27.2–28.3 GPa) were obtained in mixtures including coarse RCA, even at 100% replacement levels. The use of RCA did not significantly increase the drying shrinkage of concrete. It was shown that the use of RCA significantly reduced the cracking risk of concrete from "high" to "moderate-high" when incorporated into a high cracking risk mixture.